Safety, Pharmacokinetics, and Pharmacodynamics of Etavopivat (FT‐4202), an Allosteric Activator of Pyruvate Kinase‐R, in Healthy Adults: A Randomized, Placebo‐Controlled, Double‐Blind, First‐in‐Human Phase 1 Trial. Issue 5 (12th January 2022) - Forsyth, Sanjeev; Schroeder, Patricia; Geib, James; Vrishabhendra, Leela; Konstantinidis, Diamantis G.; LaSalvia, Kari; Ribadeneira, Maria D.; Wu, Eric; Kelly, Patrick; Kalfa, Theodosia A.
Abstract: Etavopivat (FT‐4202) is an orally administered, small‐molecule allosteric activator of erythrocyte pyruvate kinase‐R (PKR) in clinical development for the treatment of sickle cell disease and other hemoglobin disorders. This randomized, placebo‐controlled, double‐blind, first‐in‐human combination single‐ascending dose and multiple‐ascending dose phase 1 trial (NCT03815695) evaluated the safety and pharmacokinetics/pharmacodynamics of etavopivat in 90 healthy adult subjects. In 4 single‐ascending dose cohorts, 8 participants were randomized 3:1 to a single oral dose of either etavopivat (n = 6) or placebo (n = 2). In four 14‐day multiple‐ascending dose cohorts, 12 participants were randomized 3:1 to 14 days of etavopivat (n = 9) or placebo (n = 3). In these studies, most treatment‐emergent adverse events were of mild severity (grade 1) and none led to study discontinuation. Etavopivat exhibited a linear and time‐independent pharmacokinetic profile (at doses ≤400 mg) and elicited the expected pharmacodynamic effects of PKR activation (decreased 2, 3‐diphosphoglycerate and increased adenosine triphosphate) and evidence of improved hemoglobin‐oxygen affinity. In addition, pharmacodynamic responses were durable with effects continuing for 48 to 72 hours after the last dose, thereby supporting once‐daily dosing. Food appeared to have no clinically meaningful effects on etavopivat exposure, thus facilitating administration with or without food. In conclusion, the evaluation of etavopivat in healthy subjects demonstrated proof of mechanism (PKR activation) without significant adverse events. This study also allowed for the selection of dose levels, projected to have an acceptable safety profile and provide therapeutic benefit, for evaluation in future trials in patients with sickle cell disease.